The effects of multiple drilling of a bone with the same drill bit: thermal and force analysis. Issue 2 (February 2022) - Tsiagadigui, Jean Gustave; Ndiwe, Benoit; Ngo Yamben, Marie-Ange; Fotio, Nzogning; Belinga, Fabrice Ella; Njeugna, Ebenezer
Abstract: Repeated use of the same drill bit during drilling wears off the cutting edges, which can lead to a significant increase in heat as a result of friction, which is harmful to a bone above 55 °C. Few previous studies have examined the effects of using the same drill bit several times, on temperature. The objective of this study was to determine the effect of each drilling on temperature and force. 72 trials were performed. A total of 24 stainless steel drill bits of ∅3.2 mm were used to drill bovine bone samples. Each drill bit was used at least 3 times. T thermocouples were used to measure temperatures during each drilling test. Possible correlations of cutting parameters were studied. Tests were performed on a test rig measuring forces and temperatures during drilling. Effects of spindle speed (N), feed rate (Vf ), and several trials (E) on temperature and forces were measured. Images of the drill bits were analyzed by digital microscopy before and after the drilling series for signs of wear. Temperatures increased significantly from E1 to E3 . They decreased moderately with Vf . The best cutting conditions were at N = 200 rpm for Vf = 60 mm/min and N = 100 rpm for Vf = 30 mm/min drilling. At N > 200 rpm, they were very high. Temperature rise is significantly related to number of drilling (E), spindle speed (N), and inversely to feed rate (Vf ). Analysis of images by digital microscopy confirmed drill bits wearing off, following the number of trials. Abstract : Drilling; Bone; Drill bits; Temperature; Thermocouple.